Multifunctional polarization tomography of birefringence networks of biological crystals - Dubolazov, O.V.; Olar, O.I.; Burkovets, D.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2015)
The results of optical modeling of biological crystals polycrystalline multilayer networks have been presented. Determined in this work are the algorithms of reconstruction of parameter distributions that describe the linear and circular birefringence. To separate manifestations of these mechanisms, we propose the method of space-frequency filtering. Criteria for differentiation of benign and malignant tissues of the women reproductive sphere have been found.